PENDAMPINGAN WORKSHOP PERAN PESANTREN SEBAGAI PRANATA SOSIAL DAN PENGGERAK PEMBANGUNAN NASIONAL - Kholilur Rahman; Ahmad Aziz Fanani; Imam Wahyono; Riza Faishol; Fathi Hidayah; Anis Fauzi; M. Mutamakin (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
Islamic boarding schools hold strategic potential as educational institutions, centers for human resource development, and agents of community empowerment. Nevertheless, the economic potential of pesantren has often not been optimally utilized to strengthen the economic independence of the institution and its surrounding communities. This community service program aims to enhance the understanding and skills of pesantren administrators in developing economic empowerment initiatives based on local wisdom. The program was implemented through workshops and mentoring activities for the management of Yayasan Bustanul Falah and its affiliated foundations in Banyuwangi. The methods included preparation, workshop implementation, dissemination of results, and program evaluation. The workshop was attended by 100 participants representing various educational units within the foundation. The results indicate increased awareness and a shift in stakeholders’ perspectives regarding the importance of pesantren economic development through the management of business units such as cooperatives and educational canteens. Furthermore, the program fostered information exchange and collaboration among institutions in advancing pesantren-based economic initiatives. This mentoring program has had a positive impact in strengthening the institutional capacity of pesantren as centers of community empowerment and in promoting the economic independence of pesantren-based educational institutions.